Wonderful realism and oral tradition in the popular narratives of northeastern Brazil in the Mentiras Grossas de Zé Rotinho, by João Nonon de Moura Fontes Ibiapina - Ciarlini, Erika Ruth Melo (Universidade de São Paulo - Programa de Pós-graduação em Integração da América Latina, 2019)
The literature of northeastern Brazil has a great influence of orality, works among which figure thick lies of Zé Rotinho (1977), of the author Piauí João Nonon de Moura Fontes Ibiapina. For Chiampi (2015), these regional texts compose a type of literature in Latin America, in this work analyzed as a face of marvelous realism. It studies the content of popular memory in the light of Bachelard (2008), through which we detect the coexistence with the space and customs of the place, as well as Câmara Cascudo (2012), when the tales reveal the history of the Latin American people, visible in folklore and Popular tradition.